Addiction neuroethics : the promises and perils of neuroscience research on addiction - Carter, Adrian (International research monographs in the addictions., 2012)
Research increasingly suggests that addiction has a genetic and neurobiological basis, but efforts to translate research into effective clinical treatments and social policy needs to be informed by careful ethical analyses of the personal and social implications. Scientists and policy makers alike must consider possible unintended negative consequences of neuroscience research so that the promise of reducing the burden and incidence of addiction can be fully realized and new advances translated into clinically meaningful and effective treatments. This volume brings together leading addiction researchers and practitioners with neuroethicists and social scientists to specifically discuss the ethical, philosophical, legal and social implications of neuroscience research of addiction, as well as its translation into effective, economical and appropriate policy and treatments. Chapters explore the history of ideas about addiction, the neuroscience of drug use and addiction, prevention and treatment of addiction, the moral implications of addiction neuroscience, legal issues and human rights, research ethics, and public policy. * The first comprehensive volume dealing with ethical and public policy implications of neurobiological research on addiction * Features outstanding and truly international scholarship, with chapters written by leading experts in neuroscience, addiction medicine, psychology and more *Informs psychologists of related research in neuroscience and vice versa, giving researchers easy one-stop access to knowledge outside their area of specialty.